2017
DOI: 10.1158/0008-5472.can-17-1139
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Palmitoylation Mediated by ZDHHC5 in p53-Mutant Glioma Drives Malignant Development and Progression

Abstract: Gliomas with mutant p53 occurring in 30% of glioma patients exhibit therapeutic resistance and poor outcomes. In this study, we identify a novel mechanism through which mutant p53 drives cancer cell survival and malignant growth. We documented overexpression of the zinc finger protein ZDHHC5 in glioma compared with normal brain tissue and that this event tightly correlated with p53 mutations. Mechanistic investigations revealed that mutant p53 transcriptionally upregulated ZDHHC5 along with the nuclear transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 40 publications
0
72
0
Order By: Relevance
“…Furthers studies to understand how these proteins are incorporated into EVs may yield important insights into cancer progression. Interestingly, S-EVs contain the palmitoylated form of the palmitoyl-transferase ZDHHC5, which palmitoylates EZH2, one of the major transcription factors in prostate cancer progression 55 . This suggests that prostate cancer S-EVs may promote the transformation of other cells by inducing horizontal EV transfer of EZH2; however, further investigation is required.…”
Section: Discussionmentioning
confidence: 99%
“…Furthers studies to understand how these proteins are incorporated into EVs may yield important insights into cancer progression. Interestingly, S-EVs contain the palmitoylated form of the palmitoyl-transferase ZDHHC5, which palmitoylates EZH2, one of the major transcription factors in prostate cancer progression 55 . This suggests that prostate cancer S-EVs may promote the transformation of other cells by inducing horizontal EV transfer of EZH2; however, further investigation is required.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, ZDHHC5 expression levels are not associated with overall survival, but short interfering RNA (siRNA)-mediated silencing of ZDHHC5 leads to reduced cell proliferation, colony formation, cell migration, and xenograft tumor growth [86]. By contrast, in glioma cells, high ZDHHC5 expression is predictive of poorer prognosis, and this overexpression appears to be driven by oncogenic mutations in the tumor suppressor protein p53 [87]. These results suggest that individual ZDHHC enzymes can act as either oncoproteins or tumor suppressors in a tissue-specific and/or cancer type-specific manner.…”
Section: Protein Palmitoylation and Cancer: Connecting The Dotsmentioning
confidence: 99%
“…Cancer links is defined broadly as any literature link between a ZDHHC-family member and a particular cancer, including large-scale and small-scale experimental studies, animal and cell culture studies, and clinical studies, whether functional or correlative. References: ZDHHC2[70,129,130], ZDHHC3[131][132][133], ZDHHC5[87], ZDHHC7[47,134], ZDHHC9[89,92,135,136], ZDHHC11[77,78,137,138], ZDHHC13[49,73], ZDHHC14[82][83][84][85], ZDHHC20[81], ZDHHC23[139]. HPA, Human Protein Atlas (www.proteinatlas.org/).…”
mentioning
confidence: 99%
“…1a, b, PD-L1 protein level significantly decreased upon 2-BP treatment in a dose-and time-dependent manner, suggesting that PD-L1 expression is regulated by protein palmitoylation. On the basis of prior studies, 9,11 which indicated that palmitoylation could regulate protein stability, we speculated that PD-L1 itself undergoes palmitoylation to maintain stability. To validate this hypothesis, we subjected PD-L1 Flag -expressing MDA-MB-231 (MB231-PD-L1 Flag ) and BT549 (BT549-PD-L1 Flag ) breast cancer cells to acyl-biotin exchange (ABE) assays in which free cysteine thiol groups of the proteins are irreversibly blocked by N-ethylmaleimide (NEM), whereas palmitoylated cysteines are later cleaved by hydroxylamine (HAM) and biotinylated.…”
mentioning
confidence: 99%
“…palmitoyltransferase of EZH2, significantly inhibits glioma tumor growth. 9 Thus, palmitoylation or palmitoyltransferases could be novel targets for cancer therapy. In the current study, we searched for other possible metabolic-related modifications of PD-L1 such as lipid modification, and unexpectedly discovered that palmitoylation occurred on PD-L1 and played an important role in PD-L1 stability.…”
mentioning
confidence: 99%